The course of the ‘Little Ice Age’ glacierization at Engabreen and Fonndalsbreen, Vestre Svartisen, northern Norway, using quaternary geological mapping, historical evidence and lichenometric dating - Svendsen, Sunniva Pauline Due (The University of Bergen)
Postponed access: the file will be accessible after 2021-05-29 Masteroppgave i geografi GEO350 MASV-GEOG MPGEOGR MASV-MEHA MASV-PHYG